2005
DOI: 10.1021/om050179s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of (Triphenylsilyl)imido Complexes of Titanium and Zirconium

Abstract: Titanium and zirconium (triphenylsilyl)imido complexes are available through transimination from the tert-butylimido complexes with H2NSiPh3. The useful starting material Ti(NSiPh3)Cl2(py)2 (1) is prepared in 88% yield by treatment of Ti(NBut)Cl2(py)3 with H2NSiPh3. Imido 1 is a dimer in the solid state with bridging chlorides; however, solution molecular weight studies indicate that 1 is a monomer in CH2Cl2. 1 reacts with 4,4‘-di-tert-butyl-2,2‘-bipyridine (bpy) to generate the pseudo-octahedral Ti(NSiPh3)(bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…The third pyridine ligand is disposed trans to the imido group. Bond lengths and angles are unexceptional and were found to be very similar to those observed in titanium [23,25] and vanadium [21] analogues; the titaniumnitrogen bond lengths of the imido fragment is 1.7110 (13) Functionalized organoimido complexes of titanium, that is complexes that contain additional functional groups on the imido moiety, are extremely rare. [23,30] Since we have easy access to various Ti-imido complexes from readily available amines, it was of interest to probe the tolerance of our synthetic procedure towards the presence of functional groups on the alkyl/arylamine backbone, and also to learn the stability of the resulting functionalized imido compounds.…”
Section: General Synthesis Of the Imido Complexes [Ti(=nr)-cl 2 (Nhmementioning
confidence: 83%
See 2 more Smart Citations
“…The third pyridine ligand is disposed trans to the imido group. Bond lengths and angles are unexceptional and were found to be very similar to those observed in titanium [23,25] and vanadium [21] analogues; the titaniumnitrogen bond lengths of the imido fragment is 1.7110 (13) Functionalized organoimido complexes of titanium, that is complexes that contain additional functional groups on the imido moiety, are extremely rare. [23,30] Since we have easy access to various Ti-imido complexes from readily available amines, it was of interest to probe the tolerance of our synthetic procedure towards the presence of functional groups on the alkyl/arylamine backbone, and also to learn the stability of the resulting functionalized imido compounds.…”
Section: General Synthesis Of the Imido Complexes [Ti(=nr)-cl 2 (Nhmementioning
confidence: 83%
“…[10b,12d, 25,29] When dissolved in pyridine, bis-dimethylamine adducts 1 are instantly and generally quantitatively converted into tris-pyridine complexes [Ti(=NR)Cl 2 (Py) 3 ] (2). In a few cases, it has been reported that the substitution of NHMe 2 ligands by pyridine is difficult or produces mixed NHMe 2 -pyridine adducts.…”
Section: General Synthesis Of the Imido Complexes [Ti(=nr)-cl 2 (Nhmementioning
confidence: 99%
See 1 more Smart Citation
“…The silane 21 itself was prepared from triphenylsilyl chloride and ammonia. 3 In the case of sulfonamide 27 , this conversion was accomplished without the use of solvent. Thus, the byproduct trimethylsilyl chloride can be distilled off directly and recovered in greater then 75% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Each salt reveals a polydecker arrangement, best described as m,Z 1 :Z 4 , m,Z 2 :Z 3 and m,Z 2 :Z 2 for lithium, sodium and potassium, respectively. 87 Work with ZrNa systems has also been extended to the preparation of the novel organometallic sphere [{(Bu t C 5 H 4 )(Bu t C 5 H 3 )Zr(m-H)Na} 2 Á OEt 2 ] 2 through the sodium reduction of (Bu t C 5 H 4 ) 2 ZrCl 2 . Reaction of this with Bu t Li/tmeda has afforded the monolithiation of both rings, as evidenced by the crystal structure of the thf-solvate (Z 5 -C 5 H 4 Li)(Z 7 -C 7 H 6 Li)Cr Á 8thf.…”
Section: Cyclopentadienyl and Related Derivativesmentioning
confidence: 99%